Efficacy of vaccination with tumor-exosome loaded dendritic cells combined with cytotoxic drug treatment in pancreatic cancer - Xiao, Li; Erb, Ulrike; Zhao, Kun; Hackert, Thilo; Zöller, Margot (OncoImmunology, 2017)
Pancreatic cancer (PaCa) has a dismal prognosis and adjuvant immunotherapy frequently is of low efficacy due to immunosuppressive features of PaCa and PaCa-stroma. We here explored, whether the efficacy of vaccination with tumor-exosome (TEX)-loaded dendritic cells (DC) can be improved by combining with drugs affecting myeloid-derived suppressor cells (MDSC). Experiments were performed with the UNKC6141 PaCa line. UNKC6141 TEX-loaded DC were weekly intravenously injected, mice additionally receiving Gemcitabine (GEM) and/or ATRA and/or Sunitinib (Sun). UNKC6141 grow aggressively after subcutaneous and orthotopic application and are consistently recovered in peripheral blood, bone marrow, lung and frequently liver. Vaccination with DC-TEX significantly prolonged the survival time, the efficacy of DC-TEX exceeding that of the cytotoxic drugs. However, ATRA, Sun and most efficiently GEM, sufficed for a pronounced reduction of MDSC including tumor-infiltrating MDSC, which was accompanied by a decrease in migrating and metastasizing tumor cells. When combined with DC-TEX vaccination, a higher number of activated T cells was recovered in the tumor and the survival time was prolonged compared with only DC-TEX vaccinated mice. As ATRA, GEM and Sun affect MDSC at distinct maturation and activation stages, a stronger support for DC-TEX vaccination was expected by the drug combination. Intrapancreatic tumor growth was prevented beyond the death of control mice. However, tumors developed after a partial breakdown of the immune system by the persisting drug application. Nonetheless, in combination with optimized drug tuning to prevent MDSC maturation and activation, vaccination with TEX-loaded DC appears a most promising option in PaCa therapy.